Pengaruh Konsentrasi Pupuk Organik Cair Bonggol Pisang terhadap Pertumbuhan dan Hasil Tanaman Viola (Viola tricolor L.) - Wijana, Gede; Mayadewi, Ni Nyoman Ari; Mamo, Maria Paskalia (Agrotrop : Journal on Agriculture Science; Vol 14 No 3 (2024)DO - 10.24843/AJoAS.2024.v14.i03.p02, 2024)
Effect of Banana Weevil Liquid Organic Fertilizer Concentration on the Growth and Yield of Viola ( Viola tricolor L.). Ornamental plants are commodities that have high economic value and potential for cultivation. One of the cultivated ornamental plants is the viola ( Viola tricolor L.). Besides being an ornamental plant in pots, the plant is also used as an edible flower. Efforts to increase the growth and yield of viola plants are by fertilizing using liquid organic fertilizer (LOF) banana weevils. The purpose of this study was to determine the concentration and find the best concentration of banana weevil LOF on the growth and yield of viola plants. This study used a one-factor Completely Randomized Design (CRD) with 5 concentration treatments, namely 0 ml/l, 20 ml/l, 40 ml/l, 60 ml/l, and 80 ml/l, each repeated 5 times. The results showed that the application of banana weevil LOF had a very significant effect on the growth and yield of viola plants. The concentration of 80 ml/l banana weevil LOF gave the best results on plant height, number of leaves, leaf area, number of branches, number of flowers, flower diameter, fresh weight of flowers, total soluble solids, fresh weight of the stroller, and dry weight of the stroller.